Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/bc034180o
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and in Vivo Distribution after Direct Delivery of PEG−Camptothecin Conjugates to the Rat Brain

Abstract: Low water solubility and rapid elimination from the brain inhibits local delivery via implants and other delivery systems of most therapeutic drugs to the brain. We have conjugated the chemotherapy drug, camptothecin (CPT), to poly(ethylene glycol) (PEG) of molecular weight 3400 using previously established protocols. These new conjugates are very water-soluble and hydrolyze at a pH-dependent rate to release the active parent drug. We have studied the uptake of these conjugates by cells in vitro and quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 20 publications
(34 reference statements)
2
50
0
Order By: Relevance
“…Diffusion and elimination properties in brain tissue have previously been reported for a variety of compounds, including our recent measurements for camptothecin (5). These drugs have low molecular weights (below 500, except for paclitaxel), and are fairly hydrophobic (except sucrose), making them susceptible to rapid elimination through capillaries.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Diffusion and elimination properties in brain tissue have previously been reported for a variety of compounds, including our recent measurements for camptothecin (5). These drugs have low molecular weights (below 500, except for paclitaxel), and are fairly hydrophobic (except sucrose), making them susceptible to rapid elimination through capillaries.…”
Section: Introductionmentioning
confidence: 71%
“…Conjugation extends circulation time in the bloodstream, and additional attachment of protease-specific sequences can target release of the free drug. Recently, we have shown that conjugation of camptothecin to PEG can dramatically improve solubility and penetration through tissue (5).…”
Section: Introductionmentioning
confidence: 99%
“…There are two hydroxyl groups in the structure of HCPT: one aromatic (10-OH) and one aliphatic . Although the 20-OH could be grafted by PEG derivatives, [18][19][20][21][22][23] its reactivity is much less than 10-OH due to the steric hindrance. 24 The HCPT spot by TLC plate was yellow at 365 nm.…”
Section: Results and Discussion Synthesis Of Mpeg 1000 -Hcpt Conjugatementioning
confidence: 99%
“…[15][16][17] PEGylated CPT [18][19][20] or mPEG 1000 -HCPT 21 have been synthesized and evaluated in vitro and in vivo. So far, only a few studies have used a PEGylated drug as carrier to further encapsulate drugs, but the drug payload was limited (20%) in the resultant liposome-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several chemotherapeutic agents have been conjugated to PEG with covalent bonds, including a PEG-curcumin conjugate, a PEGpaclitaxel conjugate, and a PEG-camptothecin conjugate, resulting in homogeneous water-soluble prodrugs with an extended circulatory life and altered biodistribution. [26][27][28][29] Tang et al 30 reported that using PEG as a water-solubilizing unit was a useful strategy for increasing the water solubility of gambogic acid, which is hydrophobic. Ding et al 31 synthesized a series of gambogic acid-PEG conjugates with different amino acid and dipeptide spacers, which showed satisfactory water solubility compared with gambogic acid, and the circulatory retention time, biodistribution, and bioavailability of the conjugates were remarkably improved.…”
Section: Introductionmentioning
confidence: 99%